Evaluation of Etiological Causes of Hypothyroidism among Patients Visiting Specialized Center for Diabetes and Endocrinology - Alnidawi, Badri Fadhil; Abdul Jabar, Mohammed (AL-Kindy College Medical Journal, 2013)
Background: Many structural or functional abnormalities can impair the production of thyroid hormones and cause hypothyroidism.Objectives: to identify the main etiological causes of hypothyroidism among patients visiting Specialized Center for Diabetes and Endocrinology.Methods: This study was conducted in the Specialized Center for Diabetes and Endocrinology on 217 patients with proved hypothyroidism, from 2006 to 2008. Every patient was tested with thyroid function tests, Ultrasound examination, thyroid autoantibodies, fine needle aspiration, radiology of skull, isotopes scan, also checking adrenal and gonadal function. Results: Out of these 217 patients 120 patients have thyroiditis 33 patients had been undergone thyroidectomy. 39 patients had received radioactive iodine, 19 patients had congenital causes. One patient had Pituitary cause, 5 patients had graves diseases.Conclusions: It was found that the common causes of hypothyroidism are either chronic autoimmune thyroiditis or destructive treatment for thyrotoxicosis. The results of this study suggest an increase in autoimmune thyroid disease similar to the rising prevalence of type1 DM possibly indicating a rising incidence of autoimmunity in young people